Analysis of Land Use of Agricultural Sector in Improving GRDP of East Lombok Regency, Indonesia - Masril, Belia Laksmi (Sumatra Journal of Disaster, Geography and Geography Education, 2018)
The purpose of this research was to understand changes of agricultural land, contribution of agriculture sector to Gross Regional Domestic Produk (GRDP) and policy direction of agricultural GRDP in East Lombok Regency. The research method was a descritive quantitative research design. This research was conducted through secondary analysis. Technique of data analysis was GIS Analysis conducted on ArcGIS software to obtain data in respect of changes of land use from agricultural area to built-up area in East Lombok Regency. Meanwhile, policy direction of agricultural GRDP was processed by using AHP (analytic hierarchy process) technique. The results obtained were: 1) Changes of land use from Agricultural to built-up area in East Lombok Regency had been increasing since 2012 to 2015 in term of land area which was used to be used for tobacco plantations, 2) Agricultural contribution to GRDP is 27,95%. 3) 5 policy priorities toward agricultural GRDP with regard to land use changes in East Lombok are: (1) Controlling import and supporting export of farming, (2) The availability of a firm set of rules supported by accuracy of land use mapping and data collection, (3) Society’s role in improving economy, (4) The sinergy between government, farmers, and private parties, and (5) Modern agriculture based on local wisdom.